Tipologi Lahan Basah Untuk Pengembangan Tanaman Palawija (Studi Kasus Di Wilayah Pesisir Kabupaten Kubu Raya) - Bambang Widiarso (Fakultas Pertanian Universitas Tanjungpura, 2011)
Marine and Coastal Area which + 28 % of total areas in Kubu Raya Distric has potentially profit areas for palawija crops, e.a: corn, soybeans, cassavas, and sweet potatoes crops. but not yet to be specified in local uniqueness land characteristics to reach more larger productivity. These research is proposed to its clustering through Spatial Analysis with GIS, Principal Component Analysis (PCA). About 3 indexes from 13 land characteristics has been clustered, (1) K, Na, Ca, Mg and Base Saturation, have positive correlation (coefficient determination = 0,92) to corn and soybean crops productivity. (2) Cation Exchange Capacity and Silt Fractions have negative correlation (coefficient determination = 0,92) to cassava productivity. And (3) Phosfor indexes have positive correlation (coefficient determination 0,91) to sweet potatoes crops productivity